Pendalungan Culture as the Root of Character Education Entrepreneurship - Hairunisya, Nanis (Journal of Asian Scientific Research, 2014)
This study aims to explore and reconstruct values and behaviors of Pendalungan Society that can be used for entrepreneurship character education. The research method used is grounded research, with three stages of data collection Open Sampling, relational, and differentiator. Analysis methods used are open, axial and selective coding. The meanings of Pendalungan’s culture application by the traders are shown by the positive and negative of their attitude and behavior. The positive value and behavior that found are the original Indonesian cultural values that can be used in character education entrepreneurship.